Sikap dan Keterampilan Sosial dalam Menerima Kebudayaan Baru pada Masyarakat Pesisir Kecamatan Ayah Kabupaten Kebumen - Wulandari, Erfina Ayu; Purnomo, Arif; Hermanto, Fredy (Universitas Negeri Semarang, 2020)
Coastal societies are defined as the unity of collective social people living in coastal areas. Coastal societies are still very thick with their culture. As time goes by, the times are growing so that lead to the development of new cultures, including the new culture in coastal societies. The attitudes of the coastal societies towards the new culture are to accept the new culture, but the coastal societies also reject new cultures that are deemed incompatible with the culture that already exist in coastal societies. The social skills of coastal societies towards a new culture are to keep upholding existing cultural values. So that, even though a new culture develops in coastal societies, coastal communities still keep upholding existing cultural values inherited from generation to generation. Ayah District is one of the districts in Kebumen Regency. Ayah District is one of the districts whose southernmost border is the Indian Ocean. So that, some of the people in Ayah District are coastal societies. Ayah culture is very diverse, ranging from language, knowledge systems, social organizations, living equipment systems and technology, living systems, religious systems and arts are still very thick with old culture. As time goes by, the times are growing so that lead to the development of new cultures, including the new culture of coastal societies in Ayah District. The purpose of this study was to find out how the attitudes and social skills of coastal societies in the Ayah District towards the existence of a new culture that is increasingly developing. The research method applied in this study is a qualitative method. The source of data in this study is the coastal society of the Ayah District considered and trusted to know the problem to be studied. Informants in this research are Village Heads, Community Leaders and Fishermen. Data collection techniques applied by using observation, interviews, and documentation studies. Data analysis applied was interactive model analysis.